Clinging to the Edge of Chaos: The Emergence of Practice in the First Year of Teaching. Issue 7 (July 2018) - Strom, Kathryn J.; Martin, Adrian D.; Villegas, Ana MarÍa
Background/Context: New teachers must cope with various instructional, personal and organizational challenges, an experience that often leads to difficulties enacting innovative, student-centered instructional practices learned in their preservice programs and contributes to high rates of teacher attrition. Purpose: Drawing on complexity theory, this review of empirical research takes an organizational or "systems" perspective on the experiences of first-year teachers as they transition from preservice education to the teaching profession. In so doing, we aim to shift away from constructions of the teacher as an autonomous actor and instead build a more complex, nuanced, and layered understanding of the multidimensional influences that work together to shape the practices of novice teachers. Research Design: We conducted a metasynthesis of 46 studies that met the following criteria: (a) were focused on first-year teachers, (b) offered sufficient description of participants' professional practices, (c) featured participants who attended a university-based preparation program, and (d) were conducted since 1990. We first recorded each study's methods, findings, and descriptions of first-year teacher practices. As a second level of analysis, we used a complexity lens to identify the systems comprising first-year teacher practices, noting how those systems and their component or elements interacted to shape first-year teaching. Findings/Results: We found that common patterns of interactions between and among systems of first-year teaching—including the teacher herself, the classroom, the school, and the larger district, state, and federal environments—tend to reinforce traditional, teacher-centered practices. Yet, in some studies, conditions surfaced that enabled participants' to enact student-centered and equity-minded teaching practices learned in their preservice programs. Conclusions/Recommendations: Authors suggest that taking a complex systems view of beginning teaching, rather than singularly focusing on the teacher's actions out of context, can reveal opportunities for fostering more supportive, enabling conditions for new teachers to enact innovative practices that many preservice programs promote and experience a smoother transition into teaching.